One Stage Surgical Management for Third Degree Recto-vaginal Laceration in Mares: A Report of Two Cases - Pooniya, R; Jhamb, DK; Saini, R; Kumar, Satveer; Sharma, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Rectovaginal lacerations in the mare occur during parturition when the foal’s limb(s) or head are forced caudal and dorsal. The injury is seen predominantly in primiparous mares and is usually due to violent expulsive efforts by the mare (Colbern et al., 1985; Turner and McIlwraith, 1989). The injury is also seen following forced extraction of a large fetus or extraction before full dilation of the birth canal. Third-degree perineal lacerations occur when there is tearing through the rectovaginal septum, the musculature of the rectum and vagina, and the perineal body. The communication between the rectum and vagina results in the constant presence of fecal material in the vagina. Reconstruction of third-degree rectovaginal lacerations is necessary to return the mare to breeding soundness. Generally, surgery is not performed on an emergency basis. The torn tissues are edematous and grossly contaminated; and it is advisable to wait a minimum of 4 to 6 weeks before attempting a repair (Turner and McIlwraith, 1989). Various surgical techniques have been described for repairing this condition, including repairs in one or two stages (Colbern et al., 1985; Belknap and Nickels 1992). This paper describes the six bite suture pattern technique (Goetz technique) for repairing the third-degree rectovaginal laceration in mare in one stage.